Removal Of Heavy Metals By Using Aquatic Plants - Limnocharis Flava In Constructed Wetlands For Wastewater Treatment - Mhm Said, Rosli (UNIVERSITI TEKNOLOGI PETRONAS, 2014)
Wetlands with aquatic plants have been widely used in industry as the treatment for wastewater because of the availability of the wetland and the costs for maintenance and construction is quite low compared to the others. It is also has been proven to be effective in removing heavy metals from the wastewater compared to other technology that is available. In this project, the effectiveness of aquatic plants - Limnocharis Flave is going to study by building a laboratory-model size for the treatment. The experiment will be done with a reactor tank contains aquatic plants and the other one is without aquatic plant as the control. The sample of the aquatic plants (leaf, stem and roots) is going to analyze at the beginning and end of the experiment. In addition, the sample of the wastewater will be taken at the sedimentation tank and will be study and analyze by using atomic absorption spectroscopy. It is observed that greater reduction of heavy metals is achieved with treatment of limnocharis flave with the highest percentage is iron with 61.73%, followed by lead (60.79%) and nickel (35.84%). For without treatment of limnocharis flava, a slightly reduction of heavy metals are observed with the highest percentage is observed by lead (26.07%), followed by iron (20.21%) and nickel (12.37%). Analysis is also been done to the parts of plants - to study the accumulation of heavy metals at different parts of plant and roots have the highest accumulation of heavy metals and followed by stems and leaves. Thus, it can be concluded that limnocharis flava have the potential to reduce heavy metals from wastewater and roots are the most beneficial for photostabilisation of metal contaminants.